Motion capture security system using Raspberry Pi - Shaira Amira, Mohd Salleh (Universiti Malaysia Sarawak (UNIMAS), 2015)
The development of an efficient real time video motion detection system is to motivate the potential for deployment in the areas where security is focused as the main concern. Video Motion Detection Security Systems (VMDss) have been available for many years in the industry. Motion detection is known as a feature that allows the camera to detect any movement in front of it and the image of the detected motion is sent to the user. Several techniques for the motion detection have been proposed and widely used based on three approaches which is background subtraction, optical flow and temporal differencing. Furthermore, this method is known as a highly adaptive to dynamic environments which it is suitable for present application with certain modification. Currently, advanced surveillance systems are available in the market at a very high cost. Therefore, this project aims at the low cost of the efficient security program that developed the motion detection security system using Raspberry Pi. The Pi and camera are in a ready state, the main work of this project is to write a program to achieve the objectives in order to solve the entire problem or limitations.